Design Space Exploration for an IoT Node: Trade-Offs in Processing and Communication - Irida Shallari; Isaac Sanchez Leal; Silvia Krug; Axel Jantsch; Mattias O'Nils (IEEE Access, 2021)
The proliferation of smart sensor nodes for IoT deployments comes with requirements of energy efficiency and to fulfil functional requirements, but it also demands a fast time to market. As a result, we need to facilitate the design of these IoT nodes, while providing the required performance. In this article, we introduce a design space exploration method focusing on IoT nodes that are data intensive due to the inherent complexity of their high data volume. The proposed method aims to identify areas of the design where processing optimisation would have a greater impact on the overall node energy consumption, define an energy budget for prospective additional tasks in the processing pipeline, and in conclusion evaluate the optimal node offloading configuration.